Dr. Quinn medicine woman. The complete season six [videorecording (DVD)]. - Seymour, Jane, 1951-; Lando, Joe, 1961-; Allen, Chad, 1974-; Bowman, Jessica, 1980-; Toovey, Shawn; Bean, Orson (A & E Television Networks, 2011)
With Sully and a growing family to support her, each episode of the final season features a rich cast of characters and memorable storylines that bring the timeless themes of the Old West straight into the hearts of contemporary viewers. The following 22 episodes from the final season are rich with tales of courage, romance, and important family values. Bonus features: commentary with Jane Seymour and James Keach on the episode 'Point Blank,' and cast biographies. This title has been repackaged.